Genome-wide association study (GWAS) reveals key loci associated with rhizoctonia aerial blight resistance in soybean: Genome-wide association study (GWAS) reveals key loci associated with rhizoctonia aerial blight resistance in soybean - RISHIRAJ RAGHUVANSHI; SHUBHAM BIRLA; NAGARAM; RUCHA KAVISHWAR; S NISHTH; RUCHI SHROTI; LAXMAN SINGH RAJPOOT; V NATARAJ; SUBHASH CHANDRA; GIRIRAJ KUMAWAT; GYANESH K. SATPUTE; SHIVAKUMAR; et al. (Journal of Oilseeds Research, 2023)
Rhizoctonia Aerial Blight (RAB) is caused by Rhizoctonia solani is one of the most worldwide devastating diseases in soybean. In present study, a GWAS was conducted for rhizoctonia aerial blight (RAB) resistance by using 269 diverse soybean genotypes for two consecutive year 2020 & 2021. GWAS analysis revealed two most significant SNPs, located very close each other on chromosome 12 (3193687 & 3193885) and 16 (6074131 & 6076330). Some candidate genes such as related to leucine-rich repeats containing (LRRNT; Glyma.16g064200), protein ubiquitination (F-box-like) and amino acid transmembrane transport (Trp_Tyr_perm; Glyma.16g062500 & Glyma.16g062600) were identified near the significant SNP positions. Our findings may be relevant for future studies and provide insights into the genetic basis for RAB resistance in soybean.